(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article presents some thoughts on the role and place of the Jadids in forming the thought of national identity and national upgradation of young people. The article analyzes the work of the Jadids on national upgradation and preservation of national identity and the people’s self-awareness during the Jadids’ era, as well as their socio-political and cultural activities. At the same time, the works of such representatives of Jadidism as A.Avloniy, M.Bekhbudiy, A.Fitrat, in glorifying national values, promoting the achievements of modern science, and revitalizing social thought are studied.